Human Talent and its importance in MSMEs in Mexico - Beatriz Diaz Diaz; Gutiérrez, M.A. Gladys Elena Mateos; Álvarez, Dra. Aída Dinorah García (IJRDO - Journal of Business Management, 2022)
Human talent plays an important role in any entity since these are composed of people and are the ones that give life to the company and to take the good development of intellectual capital is to take advantage of those talents they possess, to exploit those knowledge, skills, skills, creativity, potentiality, helps to make MSMEs more competitive regardless of the turn or size to which it is dedicated. The purpose of this document is to identify elements that influence human talent. To this end, a quantitative research was carried out in which it was analyzed through statistical analysis that factors have been propitiated in a Recreational Company within which areas such as; Organizational development, leadership, training, emotional salary and organizational climate where it is framed that having trained, motivated, committed and self-realized people will affect the company to be productive since they are these that lead to the objectives and goals proposed. In this way turning human talent as an agent of change and success.